ANALISIS LITERASI KEUANGAN PELAKU UMKM - Ardila, Isna; Sembiring, Masta; Azhar, Elfi (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Financial literacy is the understanding or ability of a person to measure financial concepts and have the ability to manage finances well. Financial literacy is very much needed by MSME players in managing their business finances. This study aims to describe the level of financial literacy of MSME actors in making financial decisions which are categorized into not literate, less literate, sufficient literate and well literate. This research is a descriptive study with survey techniques. The research sample was 30 MSMEs consisting of the manufacturing sector, the service sector, the trade sector and the agricultural sector in Medan Marelan Regency. The data used in this study are primary data. Data collection techniques in this study were interviews and questionnaires. The results showed that the  level of financial literacy of MSME actors in Medan Marelan Regency was in the not literate category of 40%, less literate 25%, sufficient literate 25% and well literate 10%, and had a very high awareness of having a special saving pattern from their income.